Guidelines For Teachers Of Early Childhood Education: Learning Interaction Support Methods To Enhance Resilience In Children With Autism Spectrum - Zakiyah, Lailatuz; Patilima, Hamid (Kirana Publisher (KNPub), 2025)
This research aims to develop a guide module based on the learning interaction support method to enhance the resilience of children with autism spectrum. The research method employed is research and development (R&D) using a qualitative and quantitative (mixed methods) approach following the ADDIE development model. This research is conducted at TK AL-IMAN located at Jl. Airlangga 52 A Jelak Ombo, Jombang, East Java. The process of developing the guide module based on the learning interaction support method involves several stages, starting from needs analysis, design, prototype creation, to limited trials. Data is collected through observations and interviews conducted with teachers, parents, and children at TK AL-IMAN . The research results indicate 1) The needs analysis shows that the majority of children with ASD in TK AL-IMAN have low to moderate levels of resilience, with difficulties in emotional regulation, adapting to changes, and building social interactions. Teachers require more systematic guidance in implementing the Learning Interaction Support method. 2) The developed module demonstrates a very good level of feasibility based on expert validation, 3) There is a significant increase in the resilience levels of children with ASD after using the module. The aspects of ease of use, suitability for children's needs, implementation time, and the appeal of the module received positive evaluations from the teachers. These findings contribute significantly to the development of inclusive learning methods, particularly in the context of enhancing the resilience of children with ASD. The developed module not only meets practical needs in the field but also provides a strong theoretical foundation for the development of similar interventions in the future.